More general all-purpose verbs in children with specific language impairment? evidence from Greek for not fully lexical verbs in language development - Kambanaros, Maria; Grohmann, Kleanthes K. (My University, 2014)
This paper addresses verbal performance and overuse of “not fully lexical verbs” by children with specific language impairment (SLI) and peers with typical language development (TLD). Experimental data come from picture-naming and retell narratives. Fourteen school-aged children with SLI (mean age = 6 years, 9 months) participated alongside 50 language- and age-matched peers with TLD. The results revealed that children with SLI do not use light verb constructions but only general all-purpose (GAP) verbs when unable to produce single-word, specific lexical verbs. Moreover, they do not differ from language-matched TLD children in this respect. As such, GAP verbs should be viewed as symptoms of immature language or absent representations rather than impaired language. Consequently, when discussing not fully lexical verbs productions in (a)typical development, researchers should make the fundamental distinction between GAP verbs and light verbs, and focus on GAP verbs as the relevant category in SLI.
Keywords: SLI; Specific language impairment; Verbal performance